Investment potential of crowdfunding in the development of projects and entrepreneurial ventures - Đekić, Marija; Ravić, Nenad (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/028, 2021)
Crowdfunding is a popular form of financing entrepreneurial ventures, especially in America and Western Europe. Crowdfunding is an innovative way of raising money to finance projects and businesses. It is a type of alternative fundraising that involves presenting ideas that need investment, in the most convincing and original way possible, through special platforms. It belongs to the so-called FinTech new market segment, which is a combination of financial services and technology. This specific model of financing in the world is growing rapidly with the development of the Internet and social networks, which has experienced real expansion over the last decade, and now investments in this form of financing reach tens of billions of dollars a year. However, despite the importance and popularity of crowdfunding, this form of funding is not given enough attention in the professional and scientific public. Crowdfunding is an alternative to classic, bank financing. There are several different types of crowdfunding: peer-to-peer lending, equity-based crowdfunding, reward-based crowdfunding, donation based crowdfunding. Each of these types of crowdfunding provides entrepreneurs with certain benefits, i.e. advantages in relation to traditional bank financing. When it comes to the type of crowdfunding with the largest market (peer-to-peer lending), the main advantages over bank financing are: lower interest rates than the ones charged by banks, lower transaction costs, connecting with investors without an active intermediary, shorter administrative and formal procedures, because there is no extensive paperwork and guarantees and guarantors requirements, etc.